Access to and Usage of Javanese in Mass Media among Yogyakarta Youth - Udasmoro, Wening; Sulistyowati, Sulistyowati; Firmonasari, Aprillia; Astuti, Wulan Tri (Universitas Sanata Dharma, 2023)
The purpose of this study is to explore the active and passive usage of the Javanese language by youths aged 10 to 17 in the Special Region of Yogyakarta. Conducted in the province's five territorial units of Bantul Regency, Sleman Regency, Kulon Progo Regency, Gunung Kidul Regency, and Yogyakarta City, the specific objective is to determine the extent to which children and adolescents use mass media — particularly television, radio, and social media — as instruments to access contents in Javanese. It is crucial to examine how the constant flow of information affects their exposure to Javanese on various platforms as well as their use of the language on social media This quantitative study surveyed 330 elementary, junior high, and senior high school students from both public and private schools in the province’s rural and urban areas. Similarly, despite its popularity, social media has yet to be used to the maximum by Yogyakarta youth to access content in Javanese or as a means to express the language — a setback created by the dominance of the Indonesian language.